Learning Design and Implementation of Indonesia’s Merdeka Curriculum in Primary Education: A Fourth-Grade Case Study - Anisa Eka Aulia; Cristie Meilina; Dhea Putri Zahra; Farika Dwi Jayanti; Khairunnissa Khairunnissa; Neli Gusfina; Marsanda Alpriani; Laila Rahmawati (Journal of Educational Review and Research, 2024)
This study analyzes the design, planning, and implementation of Indonesia's Merdeka Curriculum in fourth-grade instruction at SDN 6 Langkai, Palangka Raya. Employing a qualitative case study approach, data were collected through classroom observations, semi-structured interviews with fourth-grade teachers, and documentation of instructional modules and learning materials. Data analysis followed the Miles and Huberman model, comprising data reduction, data display, and conclusion drawing. Findings reveal that teachers adopted a pragmatic approach by adapting instructional modules from online resources, employing diverse teaching methods (discussions, lectures, games, assignments), and implementing spontaneous differentiation. However, integration of Higher-Order Thinking Skills (HOTS) and Technological Pedagogical Content Knowledge (TPACK) remained minimal due to insufficient technological infrastructure. Key challenges included low student motivation, insufficient textbooks, and disparities in digital access. Assessment practices predominantly emphasized summative rather than formative evaluation. Nevertheless, teachers demonstrated considerable creativity in adapting instructional strategies to local contexts. The study recommends continuous professional development, infrastructure enhancement, and systemic support for effective Merdeka Curriculum implementation.